Extraction of high-quality grade cellulose and cellulose nanocrystals from different lignocellulosic agri-food wastes - Rovera, Cesare; Carullo, Daniele; Bellesia, Tommaso; Büyüktaş, Duygu; Ghaani, Masoud; Caneva, Enrico; Farris, Stefano (Frontiers in Sustainable Food Systems, 2023)
Introduction Prompted by the increasing need for an intensified valorization of agri-food waste, in this work a three-step chemical procedure was used to extract high-purity cellulose from garlic stalk, corncob, and giant cane cut-up by a sequential removal of hemicellulose, lignin, ash, and organic compounds. Cellulose nanocrystals of potential interest for nanocomposite applications were then obtained through acid hydrolysis. Methods The purity of the cellulose was determined employing Nuclear Magnetic Resonance and infrared spectroscopy, whereas dynamic light scattering, optical, atomic force microscopy, and transmission electron microscopy were used for morphological characterization. The high purity and crystallinity of cellulose was confirmed by comparison with the ultra-pure bacterial cellulose originating from K. sucrofermentans, irrespective of the waste used. Results and discussion At the end of the extraction procedure, cellulose yields of 35.73, 37.15, and 39.10%, for garlic stalk, corncob, and giant cane cut-up, respectively, were achieved. Dynamic light scattering and atomic force microscopy analyses showed that the length of the whisker-like nanocrystals depended on the raw material (from 100 nm up to > 2μm), while the final yield was 40–50% for all three wastes. The versatility and effectiveness of the method here proposed can be profitably used for a wide range of agro-waste feedstocks.